ORGANIZATIONAL LEARNING REQUIREMENTS IN INDUSTRIAL COMPANY: A CASE STUDY IN AL-FURAT GENERAL COMPANY FOR CHEMICAL INDUSTRIES - Sarmad Hamza Jassim; Hadeel Qasim Oleiwi (Scholars Digest Publishing, 2025)
The research seeks to find possible solutions that help companies in the problem of organizational learning by diagnosing the application gap in Al-Furat General Company in relation to the four organizational learning requirements represented by employee empowerment, knowledge sharing, environmental monitoring, and human containment. The research adopted a case study approach, so an examination form was designed for each requirement and illustrative drawings, mathematical equations, and quantitative ratios were used in analyzing the results and discussion. The research reached a set of conclusions, the most prominent of which is the weakness of the human aspects in the work carried out by the company. A clear deficiency appeared in the application of human containment. The research put forward a set of recommendations, the most prominent of which is the need for the company to emphasize the four organizational learning requirements in a balanced manner that achieves equal application of each of them and enhances the efficiency and effectiveness of organizational learning in the company.
Keywords: Organizational learning, Empowering Employees, Sharing Knowledge, Monitoring Environment, Involving Human